Flexoelectricity in ferroelectric materials. Issue 3 (23rd July 2019) - Zhou, Wanfeng; Chen, Pan; Chu, Baojin
Abstract : Flexoelectricity is a gradient electromechanical effect that exists in all solid dielectrics. The effect was first predicted in the late 1950s, but received little interest because it was expected to be small. The experimentally measured large flexoelectric response in ferroelectric ceramics led to the revival of the field in the early 2000s. In this study, the progress made in the flexoelectric field is reviewed. The authors' focus will be primarily on the experimental studies related to the flexoelectric effect. The techniques employed to measure the flexoelectric coefficients are first summarised. A compilation of the flexoelectric coefficients of different ferroelectrics reported in the literature will be presented. An unresolved issue in this field is that the measured flexoelectric coefficients in ferroelectric materials are normally much greater than the theoretically predicted values, and the mechanisms proposed to explain this issue are discussed. Finally, the efforts toward the applications of the flexoelectric effect are reviewed.